Sustainable Development in Chinese SMEs: A Comprehensive Approach to Innovation and Management - Qiong, Xie; Hizam-Hanafiah, Mohd; Yifu, Xie; Wenwen, Xu; Hamid, Roshayati Abdul; Juhdi, Noor Hasni (Journal of Ecohumanism, 2024)
This research explores the intersection of sustainable performance, innovation, and management practices in Chinese small and medium-sized enterprises (SMEs), focusing on manufacturing firms. It delves into the historical context of sustainable development (SD) and its relevance to modern business, particularly highlighting the unique challenges and opportunities faced by Chinese SMEs. Key themes include sustainability-oriented innovation (SOI) amd knowledge management (KM). The study underscores the need for integrating innovative strategies into business practices to enhance environmental, social, and economic performance. It identifies gaps in existing literature, particularly the limited understanding of the impact of SOI on sustainable performance in Chinese manufacturing SMEs, and calls for further research to explore effective KM processes tailored to China's unique context. The research aims to provide a comprehensive understanding of how these elements can synergistically promote sustainable development and competitive advantage for Chinese SMEs.